2016
DOI: 10.1016/j.surfcoat.2016.09.078
|View full text |Cite
|
Sign up to set email alerts
|

Self-lubricating Ni-P-MoS2 composite coatings

Abstract: Tribological coatings with low coefficients of friction are in high demand by various industries since they can improve machine efficiency and have an environmental impact. A self-lubricating Ni-P-MoS 2 composite coating has been successfully deposited on a mild steel substrate by electrodeposition. The effects of MoS 2 on the tribological coatings have been investigated. Compared to a pure Ni-P coating, the Ni-P-MoS 2 composite coating exhibited a dramatic reduction in friction coefficient against a bearing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 20 publications
4
51
1
Order By: Relevance
“…One reason for this is that the MoS 2 particles in the composite coating are increased as the MoS 2 concentration rises. The MoS 2 particles favor the formation of a relatively complete lubrication film on the contact surfaces during the friction process, which reduces the wear loss and friction coefficient . When the MoS 2 concentration exceeds 1.0 g/L, the wear loss tends to increase again.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One reason for this is that the MoS 2 particles in the composite coating are increased as the MoS 2 concentration rises. The MoS 2 particles favor the formation of a relatively complete lubrication film on the contact surfaces during the friction process, which reduces the wear loss and friction coefficient . When the MoS 2 concentration exceeds 1.0 g/L, the wear loss tends to increase again.…”
Section: Resultsmentioning
confidence: 99%
“…When the MoS 2 concentration is 0.5 g/L, the width of the wear scar is narrow (Figure B). This is attributed to the formation of a lubricating film by the MoS 2 particles . But the low content of MoS 2 particles is insufficient to form a complete lubricating film.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meng et al indicated that the stabilized friction coefficient of the electroless nickel coating decreased with the increasing reciprocating frequency and applied load [24]. He et al deposited a self-lubricating Ni-P-MoS 2 composite coating on a mild steel substrate by electrodeposition, and it showed less wear and oxidation than the pure Ni-P coating [25]. Recently, graphene-based coatings have presented a great prospect of application to improve the friction and wear performance of the mating pair under low and moderate loads, but the friction performance did not reach the expected performance under high loads [26][27][28].Nano-powders of Cu and Sn alloy have been commonly used as lubricating oil additives to improve tribological properties for the advantages of low shear strength and good thermal conductivity.…”
mentioning
confidence: 99%